Survivorship care experiences, information, and support needs of patients with oral and oropharyngeal cancer. (20th January 2016) - Manne, Sharon; Hudson, Shawna V.; Baredes, Soly; Stroup, Antoinette; Virtue, Shannon Myers; Paddock, Lisa; Kalyoussef, Evelyne
Abstract: Background: There is little research documenting the posttreatment experiences and needs of oral/oropharyngeal cancer survivors. Methods: In this cross‐sectional study, 92 patients with oral/oropharyngeal cancer diagnosed between 2 and 5 years prior completed a survey about oral cancer information and support needs. Results: About half retrospectively reported that they did not receive a written treatment summary. The desire for more oral cancer information was common; one‐third or more desired more information about long‐term effects, recommended follow‐up, and symptoms that should prompt contacting a doctor. Support needs were less common; only a lack of energy was rated as a significant support need. Patients who had a recurrence, did not drink alcohol, and had a greater recurrence fear desired more information. Smokers and more distressed patients reported more support needs. Conclusion: Survivors reported the desire for more oral cancer information. A desire for assistance was less common. © 2016 Wiley Periodicals, Inc. Head Neck 38 : E1935–E1946, 2016